The Origins of Trypillia Megasites - Chapman, John; Gaydarska, Bisserka; Nebbia, Marco (Frontiers in Digital Humanities, 2019)
The Trypillia megasites of Ukraine are the largest known settlements in 4th millennium BC Europe and possibly the world. With the largest reaching 320 ha in size, megasites pose a serious question about the origins of such massive agglomerations. Most current solutions assume maximum occupation, with all houses occupied at the same time, and target defence against other agglomerations as the cause of their formation. However, recent alternative views of megasites posit smaller long-term occupations or seasonal assembly places, creating a settlement rather than military perspective on origins. Shukurov et al. (2015)'s model of Trypillia arable land-use demonstrates that subsistence stresses begin when site size exceeded 35 ha. Over half of the sites dated to the Trypillia BI stage—the stage before the first megasites—were larger than 35 ha, suggesting that some form of buffering involving exchange of goods for food was in operation. There were two settlement responses to buffering:- clustering of sites with enhanced inter-site exchange networks and the creation of megasites. The trend to increased site clustering can be seen from Phase BI to CI, coeval with the emergence of megasites. We can therefore re-focus the issue of origins on why create megasites in site clusters. In this article, we discuss the two strategies in terms of informal network analysis and suggest reasons why, in some cases, megasites developed in certain site clusters. Finally, we consider the question of whether Trypillia megasites can be considered as “cities.”